Development Of Waterflood Profile Modification Using Brightwater Technology - Sugihardjo Sugihardjo (Testing Center for Oil and Gas LEMIGAS, 2005)
Water flooding, in many mature fields is facing a common problem of low sweep efficiency in the late production period. The breakthrough of injection water is very early when high permeability streaks or thief zones exist in the formation, and resulted in excessive water production. Two kind of technologies commonly are used to modify the permeability streak i.e. MPM (Microbial Profile Modification), and polymer gel with cross linkers material. A new technology which is called Bright Water has been intensively studied. Bright Water is capable of in-depth placement into high permeability streaks in the reservoir. To improve the water flood sweep efficiency, studies of examination a fluid injection design have been evaluated. The objective of this study is to set-up core flooding tests and to determine the effective- ness of the Bright Water to reduce the permeability, and also include optimization of Bright Water formulation, resistance factor determination, and gelling time evaluation.